Conversations with Mexican American Writers : Languages and Literatures in the Borderlands - Mermann-Jozwiak, Elisabeth; Sullivan, Nancy, 1949- (Book collections on Project MUSE., 2009)
Interviews with nine Mexican American authors conducted primarily in 2007.